Transmission, distribution and drug resistance-conferring mutations of extensively drug-resistant tuberculosis in the Western Cape Province, South Africa. Issue 4 (26th April 2022) - Oostvogels, Selien; Ley, Serej D.; Heupink, Tim H.; Dippenaar, Anzaan; Streicher, Elizabeth M.; De Vos, Elise; Meehan, Conor J.; Dheda, Keertan; Warren, Rob; Van Rie, Annelies
Abstract : Extensively drug-resistant tuberculosis (XDR-TB), defined as resistance to at least isoniazid (INH), rifampicin (RIF), a fluoroquinolone (FQ) and a second-line injectable drug (SLID), is difficult to treat and poses a major threat to TB control. The transmission dynamics and distribution of XDR Mycobacterium tuberculosis ( Mtb ) strains have not been thoroughly investigated. Using whole genome sequencing data on 461 XDR- Mtb strains, we aimed to investigate the geographical distribution of XDR- Mtb strains in the Western Cape Province of South Africa over a 10 year period (2006–2017) and assess the association between Mtb sub-lineage, age, gender, geographical patient location and membership or size of XDR-TB clusters. First, we identified transmission clusters by excluding drug resistance-conferring mutations and using the 5 SNP cutoff, followed by merging clusters based on their most recent common ancestor. We then consecutively included variants conferring resistance to INH, RIF, ethambutol (EMB), pyrazinamide (PZA), SLIDs and FQs in the cluster definition. Cluster sizes were classified as small (2–4 isolates), medium (5–20 isolates), large (21–100 isolates) or very large (>100 isolates) to reflect the success of individual strains. We found that most XDR-TB strains were clustered and that including variants conferring resistance to INH, RIF, EMB, PZA and SLIDs in the cluster definition did not significantly reduce the proportion of clustered isolates (85.5–82.2 %) but increased the number of patients belonging to small clusters (4.3–12.4 %, P =0.56). Inclusion of FQ resistance-conferring variants had the greatest effect, with 11 clustered isolates reclassified as unique while the number of clusters increased from 17 to 37. Lineage 2 strains (lineage 2.2.1 typical Beijing or lineage 2.2.2 atypical Beijing) showed the large clusters which were spread across all health districts of the Western Cape Province. We identified a significant association between residence in the Cape Town metropole and cluster membership ( P =0.016) but no association between gender, age and cluster membership or cluster size ( P =0.39). Our data suggest that the XDR-TB epidemic in South Africa probably has its origin in the endemic spread of MDR Mtb and pre-XDR Mtb strains followed by acquisition of FQ resistance, with more limited transmission of XDR Mtb strains. This only became apparent with the inclusion of drug resistance-conferring variants in the definition of a cluster. In addition to the prevention of amplification of resistance, rapid diagnosis of MDR, pre-XDR and XDR-TB and timely initiation of appropriate treatment is needed to reduce transmission of difficult-to-treat TB.